Annealing‐Free Thioantimonate Argyrodites with High Li‐Ion Conductivity and Low Elastic Modulus. (22nd December 2022) - Jung, Wo Dum; Kim, Ji‐Su; Kim, Young Jung; Jeong, Hyeseong; Han, Daseul; Nam, Kyung‐Wan; Ahn, Docheon; Kwon, Deok‐Hwang; Jung, Hun‐Gi; Lee, Jong‐Ho; Kim, Hyoungchul
Abstract: Although Li‐ion superconducting sulfides have been developed as solid electrolytes (SEs) in all‐solid‐state batteries, their high deformability, which is inherently beneficial for room‐temperature compaction, is overlooked and sacrificed. To solve this dilemmatic task, herein, highly deformable Li‐ion superconductors are reported using an annealing‐free process. The target thioantimonate, Li5.2 Si0.2 Sb0.8 S4 Br0.25 I1.75, comprising bimetallic tetrahedra and bi‐halogen anions is synthesized by two‐step milling tuned for in situ crystallization, and exhibits excellent Li‐ion conductivity (σion ) of 13.23 mS cm −1 (averaged) and a low elastic modulus ( E ) of 12.51 GPa (averaged). It has a cubic argyrodite phase of ≈57.39% crystallinity with a halogen occupancy of ≈90.67% at the 4 c Wyckoff site. These increased halogen occupancy drives the Li‐ion redistribution and the formation of more Li vacancies, thus facilitating Li‐ion transport through inter‐cage pathway. Also, the facile annealing‐free process provides a unique glass‐ceramic structure advantageous for high deformability. These results represent a record‐breaking milestone from the combined viewpoint of σion and E among promising SEs. Electrochemical characterization, including galvanostatic cycling tests for 400 h, reveals that this material displays reasonable electrochemical stability and cell performance (150.82 mAh g −1 at 0.1C). These achievements shed light on the synthesis of practical SEs suffice both σion and E requirements. Abstract : Highly deformable argyrodite reaching a Li‐ion conductivty of 13.23 mS cm −1 and an elastic modulus of 12.51 GPa is achieved by applying an annealing‐free mechanochemical method. An increased halogen occupancy of ≈90.67% at the 4 c Wyckoff site facilitates Li‐ion transport via the inter‐cage pathway. Simultaneously, the in situ crystallization process provides a unique glass‐ceramic structure with a 57.39% crystallinity beneficial for room‐temperature compaction.